Software Based Scalable Packet Capture Mechanism To Reduce Packet Loss - Alias, Syazwina (2019)
The advancement of packet capture technology has given a major impact in packet capture process whereby both software and hardware solutions have been designed to optimize packet capture performance. Packet capture has become more challenging by which the complexity of capturing packet occurred in high packet rates and high bandwidth which creates the need for more sophisticated packet capture mechanism in network traffic. This thesis focuses on minimizing the packet loss in high speed network in which it is one of the most challenging problem in packet capturing engine. By reducing the packet loss, it gives a significant impact in several aspects in network traffic performance particularly with related applications. In addition, reducing packet loss also one of the key performance indicators for analyzing the quality of network. Existing approaches in packet capture mechanism is not sufficiently capable to capture packet in high speed network due to some bottlenecks. Packet losses in high speed network takes place due to buffer overflow as their rate of arrival to the buffer increases. The intention of this thesis is to propose and implement a new mechanism in capturing packet to overcome the problem arises in the existing solutions. The proposed mechanism aims to alleviate buffer overflow because packet drop leads to inefficiency of packet capture performances.